Pendampingan Santri Dewasa dalam Penguatan Fikih Ibadah di Pondok Pesantren Miftahul Ulum Lumajang - Zainuddin (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2022)
This article describes the mentoring of adult students in strengthening religious jurisprudence. Adult education offers a philosophy of how an adult or student learns effectively, so students learn not only to recall the data the lecturer gives in lectures but also should be able to see a variety of phenomena beyond the facts. The major goal of this study was to find an application of andragogy in the sphere of planning and evaluation methodologies for boarders at Miftahul Ulum Lumajang. Learn more about how the andragogical ideas are being used with Miftahul Ulum Lumajang Islamic Boarding School. Students at Miftahul Ulum Lumajang s boarding school are using the model andragogy. The idea of adult education serves as the study's theoretical and conceptual foundation.